The Integration of Pupils from Different Cultures into Portuguese Primary Schools - Sousa, Barbára (2020)
This paper presents a research work about issues that elucidate the collected data related to the integration of pupils from different cultures in Portuguese primary schools, an increasingly evident reality in the educational setting. In empirical terms, a qualitative research was conducted through interviews, sociometric tests and data search involving the class teachers. These tools were applied to primary school classes in five schools belonging to a school grouping in the central region of Portugal. The data collected through the sociometric tests allow us to realise that the majority of the foreign pupils is not fully integrated in the primary school classes. However, according to the analysis of the interviews, this is not always the case, since the pupils’ answers showed that they do feel integrated. Based on the information gathered, it can be understood that most of the teachers consider the pupils to be well integrated and the parents/those in charge of their education to be able to keep up with them in the best way. Nevertheless, some shortage of information on the part of teachers was noticed concerning these pupils, which indicates an absence of communication between school and family, a situation that does not favour a more effective integration of these pupils.